2022
DOI: 10.1186/s12873-022-00614-8
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, injury characteristics and clinical outcomes of bicycle and motorcycle accidents in the under 20 population: South Korea

Abstract: Background Bicycles and motorcycles are a main means of transportation and leisure for individuals aged under 20 years in South Korea. We aimed to identify the epidemiology of injuries and describe and compare patterns of injury and clinical outcomes of two-wheel vehicle-related accidents in these individuals. Methods We analysed data obtained from the National Emergency Department Information System for 401 emergency departments (EDs) from January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Accidents caused by reckless and speeding driving, an excessive amount of individuals using the roads, an excessive population, bad road conditions, driver fatigue, and illegal immigration are the key contributors to the problem. [16] In current study 210 patents were presented. There were 54.8% males and 45.2% females.…”
Section: Discussionmentioning
confidence: 96%
“…Accidents caused by reckless and speeding driving, an excessive amount of individuals using the roads, an excessive population, bad road conditions, driver fatigue, and illegal immigration are the key contributors to the problem. [16] In current study 210 patents were presented. There were 54.8% males and 45.2% females.…”
Section: Discussionmentioning
confidence: 96%
“…Considering similar studies in the literature, Yun et al reported a helmet usage rate of 46.7% in their study. [ 14 ] A study conducted in Shanghai showed that the helmet-wearing rate among couriers was 34.14% for food delivery and 10.18% for express delivery. [ 15 ] Consistent with our study’s results, it was emphasized in this study that legal regulations regarding helmet use should be urgently implemented, as they can effectively reduce injuries and fatalities in traffic accidents.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, a 75.48% rate of lower extremity injuries was reported,[ 13 ] while Yun et al noted a frequency of lower extremity injuries of 56.9%. [ 14 ] Peek et al reported a frequency of 54% for lower extremity injuries in their study of 700 cases. [ 20 ] Craig et al observed in their study that lower extremity injuries were the most common in motorcycle accidents and were one of the main reasons for prolonged hospital stays.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations